2013
DOI: 10.1089/scd.2012.0192
|View full text |Cite
|
Sign up to set email alerts
|

Resistin-Like Molecule α Stimulates Proliferation of Mesenchymal Stem Cells While Maintaining Their Multipotency

Abstract: Resistin-like molecule a (RELMa) is highly upregulated in the lungs of mice subjected to hypoxia. It is secreted from pulmonary epithelium and causes potent mitogenic, angiogenic, and vasoconstrictive effects in the lung vasculature. By using bone marrow transplantation in mice, we previously showed that RELMa is able to increase the number of bone marrow-derived cells in lung tissue, especially in the remodeling pulmonary vasculature. The current study investigated the effect of RELMa on progenitor stem cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…This is also consistent with our observations that HIMF is upregulated in the vascular smooth muscle cells that are undergoing cell division [proliferating cell nuclear antigen (PCNA)- and/or Ki67-positive]. Other work from our laboratory supports this hyperplastic role for HIMF, as we have found HIMF to exert a marked shift in human mesenchymal cells to a dividing phenotype [64]. Because HIMF is primarily expressed during the early hyperplastic phase of chronic hypoxia and we have demonstrated that preventing such expression prevents long-term remodeling associated with chronic hypoxia [20], we hypothesize that HIMF acts as an initiating factor for pulmonary vascular remodeling.…”
Section: Discussionsupporting
confidence: 92%
“…This is also consistent with our observations that HIMF is upregulated in the vascular smooth muscle cells that are undergoing cell division [proliferating cell nuclear antigen (PCNA)- and/or Ki67-positive]. Other work from our laboratory supports this hyperplastic role for HIMF, as we have found HIMF to exert a marked shift in human mesenchymal cells to a dividing phenotype [64]. Because HIMF is primarily expressed during the early hyperplastic phase of chronic hypoxia and we have demonstrated that preventing such expression prevents long-term remodeling associated with chronic hypoxia [20], we hypothesize that HIMF acts as an initiating factor for pulmonary vascular remodeling.…”
Section: Discussionsupporting
confidence: 92%
“…Although here we found that HIMF caused EC apoptosis, we have reported previously that HIMF promotes proliferation of specific cell types by mediating the cell survival proteins Akt and ERK (27). Indeed, we have shown that low concentrations of HIMF (Ͻ10 nM) have proliferative effects on ECs (60), suggesting that HIMF has dual and separate actions depending on its concentration.…”
Section: Discussionmentioning
confidence: 45%
“…EC exocytosis components are known to mobilize stem and progenitor cells for the regeneration of an injured organ (31). Indeed, we have shown previously that HIMF causes strong proliferative activity in human mesenchymal stem cells (27), suggesting that it has separate and distinct effects on precursor cells and lung resident endothelium in response to injury. hRETN has been shown to activate ECs in cardiovascular diseases (17,58); however, this is the first report to show its effect on apoptosis, Ang2 induction, and EC-mediated SMC proliferation.…”
Section: Discussionmentioning
confidence: 90%
“…The resistin like alpha ( Retnla/RELMα/Fizz1 ) gene was one of the two targets identified in both T0 and T2 mice. Expression of RELMα is usually low in normal mouse lung, but it is greatly increased during hypoxia‐induced pulmonary hypertension, allergic airway inflammation, bleomycin‐induced lung fibrosis, and asthma . Kolosova et al .…”
Section: Discussionmentioning
confidence: 99%
“…Kolosova et al . showed that RELMa induces robust proliferation of mesenchymal stem cells (MSC) in mouse lung dependent on Pi3k/Akt and Erk activation . The gamma‐glutamyltransferase 1 ( Ggt1 ) gene was another common target in T0 and T2 mice.…”
Section: Discussionmentioning
confidence: 99%